The African-American Odyssey: (Volume.1) - Hine, Darlene Clark [et al.] (New Jersy Pearson Hall, 2006)
This 3rd edition of The African-American Odyssey includes not only a CD-ROM-bound into every book (which incorporates over 150 documents in African American history), but also has a broadened international perspective, expanded coverage of interaction among African Americans and other ethnic groups, and new material on African Americans in the western portion of the United States. Free access to Research Navigator is included. This allows readers to access this powerful research tool with one site. Written by leading scholars, The African-American Odyssey is a clear and comprehensive narrative of African-American history, from its African roots through the Civil War. Succeeding volumes carry on this theme through the modern era. This book places African-American history in the context and at the center of American History. Balancing accounts of the actions of African-American leaders with investigations of the lives of the ordinary men and women in black communities, exciting and readable coverage includes: African-American history from its African origins to the sixteenth century and the beginning of the forced migration of millions of Africans to the Americas. Succeeding chapters present the struggle of black people to maintain their humanity during the slave trade and as slaves in North America during the long colonial period. It continues through the Civil War and the beginning of Reconstruction. This is a compelling story of survival, struggle, and triumph over adversity. Readers will learn an appreciation of the central place of black people and black culture in this country, and a better understanding of both African-American and American history.
Include Colored Illustrations, Appendix and Index
Keywords: African Americans